Sustainable Development: Development of Wisdom for Dyeing Natural Fibers Used to Create Community Textile Products - Roengthanapiboon, Natthatida; Sindhuphak, Apisak; Kijmongkolvanich, Sirisyos; Egwutvongsa, Songwut (My University, 2024)
The objectives of this research were: (1) to examine the factors influencing the natural dyeing process using teak leaves, and (2) to evaluate consumer satisfaction with textiles dyed using this technique. A structured questionnaire was employed as the research instrument, focusing on the characteristics of environmentally friendly textile products. Utilizing Exploratory Factor Analysis (EFA), the study identified 28 variables affecting the natural dyeing process from teak leaves, and Confirmatory Factor Analysis (CFA) established separate discriminant validity data. Four key factors were identified: (1) Policy and Natural Materials, (2) Knowledge of Local Materials, (3) Wisdom/Skills, and (4) Textile Products. All factors met the standard criteria for fit indices, with values of χ2 = 11.164, df = 15, relative χ2 =.744, p =.741, GFI =.991, AGFI =.956, NFI =.994, TLI = 1.009, CFI = 1.000, RMSEA =.000, and RMR =.020, allowing for the evaluation of new textile product prototypes through Multiple Regression Analysis. The study found that these four independent variables collectively explained 86.0% of consumer satisfaction, as indicated by the standardized regression equation =.434(X1) +.325(X2) +.292(X3). The findings highlight the potential of using local materials to enhance environmental sustainability, generate community income, and preserve traditional wisdom in Thailand.
Keywords: Creativity; Dyeing; Natural materials; Products; Sustainability